An intermittent running test to estimate maximal oxygen uptake: the Andersen test - Andersen, L. B.; Andersen, T.-E.; Andersen, E.; Anderssen, S. A. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. Monitoring of height and weight in children in schools has been discussed to get data on trends in obesity. Physical fitness may be just as important to monitor and a simple reliable test will therefore be important. The aim of this paper was to analyze the association between .VO2max measured during maximal work on a treadmill and running distance in an intermittent running test. Methods. Three different groups conducted an intermittent running test. .VO2max was measured directly during treadmill running. The groups were 27 physical education students (age 20.0-27.0 years), 57 children (age 9.9-11.0 years), and 14 male elite soccer players (age 14.2-15.0 years). Results. The reproducibility of the Andersen test was good (r=0.84). Subjects ran 15 m (SD 61 m) longer the second time, but this difference was not significant (P=0.102). The association between running distance in the Andersen test and .VO2max measured on the treadmill showed a correlation coefficient of 0.87 in university students, 0.68 in children, and 0.60 in soccer players. For the whole group: .VO2max= 18.38 + (0.03301*distance) (5.92*sex) (boys=0;girls=1) (r=0.84). Conclusion. The test may provide teachers and health care professionals with an important tool to estimate physical fitness in children and adolescents in a fast, non-expensive and reliable way.